Evaluation of the sensitivity of the novel α4β2* nicotinic acetylcholine receptor PET radioligand 18F‐(‐)‐NCFHEB to increases in synaptic acetylcholine levels in rhesus monkeys. Issue 11 (28th July 2014) - Gallezot, Jean‐Dominique; Esterlis, Irina; Bois, Frederic; Zheng, Ming‐Qiang; Lin, Shu‐Fei; Kloczynski, Tracy; Krystal, John H.; Huang, Yiyun; Sabri, Osama; Carson, Richard E.; Cosgrove, Kelly P.
ABSTRACT Objective 18F‐(‐)‐NCFHEB (also known as 18F‐(‐)‐Flubatine) is a new radioligand to image α4β2* nicotinic acetylcholine receptors in vivo with positron emission tomography (PET), with faster kinetics than previous radioligands such as 18F‐2‐F‐A85380. The goal of this study was to assess the sensitivity of 18F‐(‐)‐NCFHEB‐PET to increases in synaptic acetylcholine concentration induced by acetylcholinesterase inhibitors. Methods Two rhesus monkeys were scanned four times each on a Focus 220 scanner: first at baseline, then during two bolus plus infusions of physostigmine (0.06–0.28 mg/kg), and finally following a bolus injection of donepezil (0.25 mg/kg). The arterial input function and the plasma free fraction fP were measured. 18F‐(‐)‐NCFHEB volume of distribution VT was estimated using the multilinear analysis MA1 and then normalized by plasma free fraction fP. Results 18F‐(‐)‐NCFHEB fP was 0.89 ± 0.04. At baseline, 18F‐(‐)‐NCFHEB VT/fP ranged from 7.9 ± 1.3 mL plasma/cm3 tissue in the cerebellum to 34.3 ± 8.4 mL plasma/cm3 tissue in the thalamus. Physostigmine induced a dose‐dependent reduction of 18F‐(‐)‐NCFHEB VT/fP of 34 ± 9% in the putamen, 32 ± 8% in the thalamus, 25 ± 8% in the cortex, and 23 ± 10% in the hippocampus. With donepezil, 18F‐(‐)‐NCFHEB VT/fP was reduced by 24 ± 2%, 14 + 3% and 14 ± 5%, 10 ± 6% in the same regions. Conclusion 18F‐(‐)‐NCFHEB can be used to detect changes in synaptic acetylcholine concentration and is a promising tracer to study acetylcholine dynamics with shorter scan durations than previous radioligands. Synapse 68:556–564, 2014. © 2014 Wiley Periodicals, Inc.